Corporate Value: Persona pada Company Profile PT. Kereta Api Indonesia - Muhammad, Alfitra Maharindra; Prawiradiredja, Sanhari; Fitriyah, Irmia (Jurnal Komunikasi Profesional, 2018)
Kereta Api Indonesia is a train state-owned holding(BUMN). They create meaning by company profile video using Youtube.  Companny profile  is a  business  that  explain  the  companny  thoroughly.  What  is  meant is  the  companys value  as well  as  the  value  of  the  products. Researches will also  discuss   about  the  content  of  the  video  and  also  provide  a  detailed  discussion  in  this  study. This  research uses  qualitative   method,  that  is  by  analytical  descriptive  method  by  looking  at  video  recording  companny  profile  of Kereta Api Indonesia.Keywords: companny profile, train, corporate value